Geogebra for teaching geometry in new school : Geogebra en la enseñanza de la geometría en escuela nueva - Franco-Saavedra, Maira Alejandra (2026)
The present article aims to analyze the benefits of GeoGebra in teaching Geometry to primary school students. The preceding research was conducted at the Centro Educativo La Bodega, Arroyo de Agua campus, in the municipality of La Paz, Department of Cesar, Colombia, an institution that operates under the Escuela Nueva model. The sample comprised the entire population, consisting of nine students from grades 1° to 5°. A mixed-methods approach was used, with a descriptive scope and data collection techniques. After identifying the needs, a didactic sequence mediated by GeoGebra was designed based on the ADDIE instructional model. Statistical analysis showed significant improvements in the analyzed dimensions.